Upaya Pencegahan Tindak Pidana Penadahan Telepon Seluler Batangan yang Berakibat Merugikan Konsumen oleh Kepolisian Resort Kota Pekanbaru - Mhd. Indra Kurniawan; Erdianto Effendi; Evi Deliana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Enforcement of criminal offenses of cellphone (cellphone) results from theft in the jurisdiction ofthe Pekanbaru City Resort Police has not been carried out effectively, and there are still many circulation ofbar cellular phones (HP) that do not have letters or assistance relations every year and follow up is difficultto improve because it avoids public awareness.The obstacle that was followed up by Pekanbaru City Resort Police in carrying out lawenforcement on criminal acts of barring cell phone (theft) from the theft in the legal area of Pekanbaru CityPolice is the price of cellphone bars (Hp) which are relatively cheap, using a sufficient distance far, lowerlegal awareness of the community, better if updated or socialized with the community, and preferred by lawenforcement.Efforts to prevent cases of theft of cellphone (cellphone) from theft in the jurisdiction of thePekanbaru City Police Resort are to reduce the theft of bar cell phone (HP), bring legal complaints to thecommunity, and increase supervision and cooperation between regional police departments aboutimposition of bar cell phones (HP) resulting from theft.